ANALYSIS OF USE ACTIVE TRANSPORTATION ON BODY MASS INDEX OF POPULATION CITY IN BANDAR LAMPUNG - Hendro Muliarto; Rizka Firdausi Pertiwi; Alhamidi Alhamidi; Fradina Agustin (TATALOKA, 2018)
Active transport is any form of human powered transportation such as walking and cycling. Active transport can reduce the risk of obesity estimated through body mass index. This study aims to determine the tendency of active transportation of the Bandar Lampung resident and its correlation to body mass reaction rate. Data were collected on 400 respondents as sample who height and weight was measured and given questionnaire. The results showed that the highest active transportation choice of respondents was walking to the workplace (22.0%) and activity at leisure time (30.3%). That value was lower than respondents who chose motorcycles (61.1% for work, 37.7% for dropping children to school, 70.4% while shopping and 50.0% for leisure activities). The was no significant correlation between the duration of walking and cycling in the last seven days to the level of the respondent's body mass index.